Structure activity investigations of XTH inhibitors - Kosonen, Juho Aleksi (UiT Norges arktiske universitet, 2019)
XTHs (xylogclucan endotransglucosylase/hydrolases) are a group of plant enzymes that regulate xyloglucan crosslinking in cell walls and play an essential role in regulation of plant growth. It is thought that XTHs play an integral role in the way the parasitic vine plant Cuscuta is able to penetrate host plant cell walls. Parasitic higher plants are a formidable threat to agricultural production around the globe, and finding new ways to fight these is essential for sustaining the world population’s need for food. Through recent research it was discovered that the triphenylmethyl food colorant Brilliant Blue R250 inhibits XTHs and the development of Cuscuta haustorium, specialized organs by which the parasite absorbs host nutrients. In this master’s thesis, the structure of Brilliant Blue R250 was used as a starting point for synthesis of potential inhibitors of XTHs. The aim was to synthesize compounds with increased activity and water solubility. A range of Brilliant Blue derivatives were synthesized and their ability to bind proteins and inhibit the endotransglucosylation activity of XTHs was tested at the Department of Arctic and Marine Biology. The project is a collaboration between Organic Chemistry and Arctic and Marine Biology at UiT.